Spatial and temporal distribution of soil-transmitted helminth infection in sub-Saharan Africa: a systematic review and geostatistical meta-analysis. Issue 1 (January 2015) - Karagiannis-Voules, Dimitrios-Alexios; Biedermann, Patricia; Ekpo, Uwem F; Garba, Amadou; Langer, Erika; Mathieu, Els; Midzi, Nicholas; Mwinzi, Pauline; Polderman, Anton M; Raso, Giovanna; Sacko, Moussa; Talla, Idrissa; et al.
Summary Background Interest is growing in predictive risk mapping for neglected tropical diseases (NTDs), particularly to scale up preventive chemotherapy, surveillance, and elimination efforts. Soil-transmitted helminths (hookworm, Ascaris lumbricoides, and Trichuris trichiura) are the most widespread NTDs, but broad geographical analyses are scarce. We aimed to predict the spatial and temporal distribution of soil-transmitted helminth infections, including the number of infected people and treatment needs, across sub-Saharan Africa. Methods We systematically searched PubMed, Web of Knowledge, and African Journal Online from inception to Dec 31, 2013, without language restrictions, to identify georeferenced surveys. We extracted data from household surveys on sources of drinking water, sanitation, and women's level of education. Bayesian geostatistical models were used to align the data in space and estimate risk of with hookworm, A lumbricoides, and T trichiura over a grid of roughly 1 million pixels at a spatial resolution of 5 × 5 km. We calculated anthelmintic treatment needs on the basis of WHO guidelines (treatment of all school-aged children once per year where prevalence in this population is 20–50% or twice per year if prevalence is greater than 50%). Findings We identified 459 relevant survey reports that referenced 6040 unique locations. We estimate that the prevalence of hookworm, A lumbricoides, and T trichiura among school-aged children from 2000 onwards was 16·5%, 6·6%, and 4·4%. These estimates are between 52% and 74% lower than those in surveys done before 2000, and have become similar to values for the entire communities. We estimated that 126 million doses of anthelmintic treatments are required per year. Interpretation Patterns of soil-transmitted helminth infection in sub-Saharan Africa have changed and the prevalence of infection has declined substantially in this millennium, probably due to socioeconomic development and large-scale deworming programmes. The global control strategy should be reassessed, with emphasis given also to adults to progress towards local elimination. Funding Swiss National Science Foundation and European Research Council.